Additive manufacturing method for copper precision device based on inorganic salt
Through the additive manufacturing method of copper precision devices based on inorganic salts, 3D printing and copper ion processing technology, the problems of coarse grains and low resolution in the existing copper additive manufacturing methods are solved, and high-resolution and high-performance copper precision devices are achieved, reducing manufacturing costs and improving production efficiency.
Patent Information
- Application Number
- CN202311307163.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-10
- Publication Date
- 2025-04-11
AI Technical Summary
The existing copper additive manufacturing methods have problems such as coarse grains, low resolution and poor physical performance of parts, which are difficult to meet the manufacturing needs of complex structures and high precision.
Using an additive manufacturing method of copper precision devices based on inorganic salts, a copper precision device hydrogel precursor is prepared by putting a loadable copper photosensitive resin into a 3D printer for 3D printing, and fully immersing it in CuSO4 solution to load copper ions, followed by thermal degreasing and copper ion reduction treatment to obtain high-resolution and high-performance copper precision devices.
The high resolution (minimum resolution reaches 40μm) and excellent mechanical properties of copper precision devices are achieved, and the problems of coarse grains and low resolution in traditional copper additive manufacturing methods are overcome, reducing manufacturing costs and improving production efficiency.
Smart Images

Figure CN119794370A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of additive manufacturing and relates to an inorganic salt-based additive manufacturing method for copper precision devices. Background Art
[0002] Pure copper and copper alloys have excellent electrical conductivity, thermal conductivity, ductility, corrosion resistance, wear resistance and other properties, and are widely used in electricity, electronics, energy and chemical industry, machinery manufacturing, transportation, light industry, aerospace and other fields. In recent years, with the rapid development of manufacturing and electrical industries, the requirements for the geometric complexity of parts structures have gradually increased, and traditional processing technology has gradually been unable to meet the needs.
[0003] Additive manufacturing technology can perfectly solve the problem that traditional manufacturing technology is difficult to produce complex parts. Compared with the traditional metal parts production through turning, cutting, milling, grinding, drilling and other machining processes to remove bulk materials, metal additive manufacturing technology is a technology that can manufacture objects of any shape without traditional tools, fixtures and processing machines. This technology has the following advantages: 1) Compared with subtractive materials, additive manufacturing can effectively reduce the processing cycle. 3D printing technology automatically, quickly, directly and accurately converts the design model into a three-dimensional entity, eliminating a series of processes such as block preparation, machining and post-processing; 2) It greatly reduces the technical threshold of the manufacturing industry. It only needs to perform intelligent design in the computer, and then convert the complex operation process into a digital file and transfer it to the 3D printer to realize manufacturing; 3) Extremely high manufacturing freedom. Due to the layer-by-layer processing and cumulative forming characteristics of 3D printing, parts with arbitrarily complex geometric shapes can be made without being restricted by the inability of tools to reach certain surfaces in traditional mechanical processing methods; 4) Nearly 100% raw material utilization rate. Theoretically, the raw material utilization rate can reach 100%, and the actual production is higher than 90%, which is much higher than the traditional manufacturing process, thereby reducing manufacturing costs; 5) "Design on demand, print on demand", parts with arbitrarily complex structures can be designed according to needs, and can be printed instantly according to real-time needs.
[0004] Additive manufacturing technology has great application potential in the preparation of pure copper or copper alloy radiators and heat exchangers, tail nozzles, motor windings and other parts with complex integrated functions. Patent CN109759589A discloses a pure copper 3D printing additive manufacturing method, which uses laser 3D printing to overcome the mold manufacturing cost, refine the grains of copper parts and obtain model parts with high precision and good forming mechanical properties, but the technology cannot achieve a resolution of less than 100μm for printing of complex copper structures and there are certain holes and defects inside. In document 1, a relatively mild laser (400W) was used for copper 3D printing to achieve a low-roughness copper heat dissipation device, but the technology does not support the manufacture of micro copper precision devices (Constantin L, Wu Z, Li N, et al. Laser 3D printing of complex copper structures [J]. Additive Manufacturing, 2020, 35: 101268.). In document 2, copper powder is mixed into photosensitive resin using digital light processing technology for copper-resistance structure design, but the direct doping of copper powder will directly affect the printing process, resulting in poor resolution and surface roughness (Li Y, LiC, Zhang X, et al. Incorporating metal precursors towards a library of high-resolution metal parts by stereolithography [J]. Applied Materials Today, 2022, 29: 101553.). However, the existing additive manufacturing processes for pure copper and copper alloys, such as powder bed, directed energy deposition, ultrasonic additive manufacturing (UC), material extrusion, photocuring, binder jetting (BJ), etc., mostly use raw materials such as copper powder, copper wire or copper sheet, which are relatively expensive. There are resolution limitations in the creation of copper complex structure devices (difficult to reach within 100 μm) and their structural strength cannot be guaranteed. Summary of the invention
[0005] In order to solve the problems of coarse grains, low resolution and poor physical properties of parts in the existing copper additive manufacturing methods, the present invention provides an inorganic salt-based copper precision device additive manufacturing method.
[0006] The technical solution of the present invention is as follows:
[0007] The method for additive manufacturing of copper precision devices based on inorganic salts specifically comprises the following steps:
[0008] (1) Preparation of copper-carrying photosensitive resin: Polyethylene glycol diacrylate oligomer with a molecular weight of 575, photoinitiator PI-819, dye lemon yellow and diluent deionized water are mixed evenly to form a copper-carrying photosensitive resin, wherein the mass of the diluent is 2-3 times the mass of the oligomer, and the added amounts of the photoinitiator and the dye are 1wt% and 0.05wt% of the oligomer, respectively;
[0009] (2) Printing of copper precision device hydrogel precursor: according to the preset model parameters of the copper precision device, the copper-carrying photosensitive resin is placed in a 3D printer for 3D printing to obtain the copper precision device hydrogel precursor;
[0010] (3) Copper ion loading: The copper precision device hydrogel precursor is fully immersed in a 0.8-1.1 mol / L CuSO4 solution and washed with water to obtain a copper-loaded organic metal structure device;
[0011] (4) Thermal degreasing treatment of the copper-loaded organic metal structure device: the copper-loaded organic metal structure device is placed in a muffle furnace, heated to 700±50°C in an air atmosphere, and organic matter in the copper-loaded organic metal structure device is removed, and then naturally cooled to room temperature;
[0012] (5) Copper ion reduction treatment of copper-loaded organic metal structure devices: The copper-loaded organic metal structure device after the thermal degreasing treatment in step (4) is placed in a tube furnace, and the temperature is raised to 900±50°C in an inert atmosphere to reduce the copper ions and further remove impurities in the device, and then naturally cooled to room temperature to obtain a copper precision device.
[0013] Furthermore, in step (2), the printing parameters are as follows: printer light wavelength: 405nm; printing layer thickness: 0.05mm; substrate light intensity: 30mW / cm 2 ; Light intensity of other layers: 10mW / cm 2 ; Exposure time of substrate: 2.5s; Exposure time of other layers: 5.5s; Platform separation speed: 3mm / s; Waiting time after separation: 5s; Post-curing time: 10min. Using the above printing parameters, the resolution of hydrogel devices can be greatly improved and the defect rate can be reduced.
[0014] Furthermore, in step (3), the concentration of the CuSO4 solution is 1.0 mol / L, the immersion temperature is 50°C, and the immersion time is 3-5 days. The immersion time depends on the structure size and shape of the hydrogel precursor. For example, a hollow porous structure can be immersed for 3 days, and a solid structure can be immersed for 5 days.
[0015] Furthermore, in step (4), the thermal degreasing treatment can remove most of the organic components in the copper-loaded organic metal structure device, thereby reducing the impurity content to the greatest extent.
[0016] Furthermore, in step (4), the insulation time is 2 to 3 hours.
[0017] Furthermore, in step (5), the heating rate is below 1°C / min, and the temperature is kept at 500°C for 2 hours. This annealing step can eliminate the internal stress of the device to a great extent and prevent the device from deformation and cracking.
[0018] Furthermore, in step (5), the insulation time is 9 to 10 hours.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] (1) The present invention adopts 3D technology and does not require molds, so it does not increase costs when manufacturing complex objects, can significantly reduce device manufacturing costs, and shorten device production cycles;
[0021] (2) The present invention can eliminate the internal stress of thin-walled devices to the greatest extent through degreasing and sintering by annealing integrated molding, and prevent device deformation. At the same time, 3D printing has the characteristics of high dimensional accuracy, good surface quality, and excellent performance of formed parts;
[0022] (3) The present invention adopts 3D printing based on copper ion inorganic salt as raw material to manufacture oxygen-free copper devices instead of traditional casting and powder metallurgy methods, which overcomes the shortcomings of coarse grains and poor performance caused by traditional casting methods, saves processing costs, improves production efficiency, and overcomes the shortcomings of traditional powder metallurgy processing methods with complicated procedures, reducing the mixing of impurities;
[0023] (4) The present invention is based on the reduction of copper ions into metallic copper, which has extremely fine grains and can greatly improve the device resolution (the minimum resolution reaches 40 μm), and obtains the mechanical properties of the copper metal structure with a hardness of 1.42±0.21 GPa (higher than the theoretical hardness). The manufactured device has high precision, good formability and high comprehensive mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of the 3D printing process of the inorganic salt-based copper precision device of the present invention (a), SEM image of the copper precision device structure surface (b) and EDX element analysis spectrum (c).
[0025] Figure 2 EBSD map of the surface of copper precision device structure (a) and nanoindentation hardness map based on Hall-Patch curve (b).
[0026] Figure 3 This is a graph showing the TGA test results of different photosensitive resins in Example 1.
[0027] Figure 4This is a structural diagram of the 3D printing model of the copper precision device hydrogel precursor 2 in Example 2.
[0028] Figure 5 The structures of the copper-loaded organic metal structure device under an optical microscope after being immersed in CuSO4 solutions of different concentrations in Example 3 are (a) 0.8 mol / L; (b) 0.9 mol / L; (c) 1.0 mol / L; and (d) 1.1 mol / L. DETAILED DESCRIPTION
[0029] The present invention is further described in detail below in conjunction with specific embodiments and drawings.
[0030] Example 1
[0031] (1) Prepare photosensitive resin 1: polyethylene glycol diacrylate (molecular weight ~575), photoinitiator (PI-819), dye (lemon yellow), diluent (deionized water). The mass of the diluent is twice the mass of the oligomer, and the amounts of the photoinitiator and dye are 1wt% and 0.05wt% of the oligomer, respectively.
[0032] (2) Prepare photosensitive resin 2: acrylamide, photoinitiator (PI-819), dye (lemon yellow), and diluent (deionized water). The mass of the diluent is twice that of the acrylamide, and the amounts of the photoinitiator and dye are 1wt% and 0.05wt% of the acrylamide, respectively.
[0033] (3) Prepare photosensitive resin 3: acrylic acid, photoinitiator (PI-819), dye (lemon yellow), diluent (deionized water). The mass of the diluent is twice the mass of acrylic acid, and the amounts of the photoinitiator and dye are 1wt% and 0.05wt% of the acrylic acid, respectively.
[0034] (4) The photosensitive resins 1, 2, and 3 are placed in a digital light processing 3D printer for 3D printing respectively. The printing parameters are as follows: printer light wavelength: 405 nm; printing layer thickness: 0.05 mm; substrate light intensity: 30 mW / cm 2 ; Light intensity of other layers: 10mW / cm 2 ; Exposure time of substrate: 2.5s; Exposure time of other layers: 5.5s; Platform separation speed: 3mm / s; Waiting time after separation: 5s; Post-curing time: 10min. The copper precision device hydrogel precursors 1, 2, and 3 were obtained respectively.
[0035] (5) The copper precision device hydrogel precursors 1, 2, and 3 were immersed in a 1.1 mol / L CuSO4 solution at 50°C for 5 days to obtain copper-loaded organic metal structure devices 1, 2, and 3, respectively. The copper ion content in the copper-loaded organic metal structure devices was observed by TGA test.
[0036] Figure 3 The TGA test results of different photosensitive resins show that the copper ion content in the copper-loaded organic metal structure device 1 is the highest, reaching 20.3wt%. Therefore, the photosensitive resin 1 is selected as the final copper-loaded photosensitive resin formula.
[0037] Example 2
[0038] (1) Prepare photosensitive resins 1, 2, 3, 4, and 5: polyethylene glycol diacrylate (molecular weight ~575), photoinitiator (PI-819), dye (lemon yellow), and diluent (deionized water). The mass of the diluent is 1.5, 2, 2.5, 3, and 4 times the mass of the oligomer.
[0039] (2) Photosensitive resins 1, 2, 3, 4, and 5 were placed in a digital light processing 3D printer for 3D printing, and the printing parameters were as follows: printer light wavelength: 405 nm; printing layer thickness: 0.05 mm; substrate light intensity: 30 mW / cm 2 ; Light intensity of other layers: 10mW / cm 2 ; Exposure time of substrate: 2.5s; Exposure time of other layers: 5.5s; Platform separation speed: 3mm / s; Waiting time after separation: 5s; Post-curing time: 10min. The copper precision device hydrogel precursors 1, 2, 3, 4, and 5 were obtained respectively.
[0040] The rationality of the photosensitive resin formula is judged by the 3D structure fidelity. Figure 4 This is a 3D printing model structure diagram of the copper precision device hydrogel precursor 2. Its maximum resolution can reach 100μm. It has high resolution and is suitable as a photosensitive resin for 3D printing.
[0041] Example 3
[0042] (1) Prepare photosensitive resin: polyethylene glycol diacrylate (molecular weight ~575), photoinitiator (PI-819), dye (lemon yellow), diluent (deionized water). The mass of diluent is twice the mass of oligomer, and the amount of photoinitiator and dye is 1wt% and 0.05wt% of oligomer respectively.
[0043] (4) The photosensitive resin is placed in a digital light processing 3D printer for 3D printing. The printing parameters are: printer light wavelength: 405nm; printing layer thickness: 0.05mm; substrate light intensity: 30mW / cm 2 ; Light intensity of other layers: 10mW / cm 2 ; Exposure time of substrate: 2.5s; Exposure time of other layers: 5.5s; Platform separation speed: 3mm / s; Waiting time after separation: 5s; Post-curing time: 10min. The hydrogel precursor of copper precision device was obtained.
[0044] (5) The copper precision device hydrogel precursor was immersed in 0.8, 0.9, 1.0, and 1.1 mol / L CuSO4 solutions at 50°C for 5 days to obtain copper-loaded organic metal structure devices. The shape fidelity of each device was observed and compared under an optical microscope. The results are as follows: Figure 5 As shown. Figure 5 It can be seen that the optimal immersion concentration is 1.0 mol / L CuSO4 solution.
[0045] Example 4
[0046] (1) Use Solidwork 3D software to create an additive 3D model, and then export the created 3D model file in STL format for subsequent layering processing and support establishment.
[0047] (2) Construct reasonable support and slices, mainly for overhanging and thin-walled structures, and add corresponding support structures to prevent deformation; the slice thickness is 0.01-0.05mm, and the appropriate layer thickness is selected according to the size and shape of the device. The Asiga digital light processing 3D printer supporting software composer can automatically slice the created STL file for subsequent layer-by-layer printing to build a precise hydrogel structure, and the software generates slice simulation layers at each level for subsequent structural enhancement and improvement, which are transmitted to the printer wirelessly.
[0048] (3) The oligomer polyethylene glycol diacrylate, the photoinitiator PI-819, the dye lemon yellow and the diluent deionized water are mixed evenly to form a copper-carrying photosensitive resin, wherein the mass of the diluent is twice the mass of the oligomer, and the added amounts of the photoinitiator and the dye are 1wt% and 0.05wt% of the oligomer, respectively.
[0049] (4) According to the preset model parameters of the copper precision device, the copper-carrying photosensitive resin is placed in a 3D printer for 3D printing to obtain a copper precision device hydrogel precursor. The printing parameters are as follows: printer light wavelength: 405 nm; printing layer thickness: 0.05 mm; substrate light intensity: 30 mW / cm 2 ; Light intensity of other layers: 10mW / cm 2 ; Exposure time of substrate: 2.5s; Exposure time of other layers: 5.5s; Platform separation speed: 3mm / s; Waiting time after separation: 5s; Post-curing time: 10min. By setting the above parameters, the resolution of hydrogel devices can be greatly improved and the defect rate can be reduced.
[0050] (5) After post-curing, the copper precision device hydrogel precursor is immersed in a 50° C., 1 mol / L CuSO4 solution for 3-5 days. After the copper ion loading is completed, the copper-loaded organic metal structure device is washed with deionized water.
[0051] (6) First, place the copper-loaded organic metal structure device in a muffle furnace, slowly increase the furnace temperature from 25°C to 700°C in an air atmosphere, and keep it at this temperature for 2 hours to remove the organic matter in the copper-loaded organic metal structure, and then naturally cool it to room temperature. The thermal degreasing step can eliminate most of the organic components in the device and minimize the impurity content.
[0052] (7) After thermal debinding, the device is transferred into a tube furnace and slowly heated from 25°C to 900°C in an inert atmosphere for 9 hours to reduce the copper metal and further remove impurities from the device. The above heating rate is as low as 1°C / min. The annealing step of 500°C for 2 hours in an inert atmosphere can greatly eliminate the stress inside the device and prevent deformation and cracking of the device. After the annealing step, the furnace chamber is naturally cooled to below 50°C, and the sample is taken out and placed in a vacuum storage to isolate the air to prevent subsequent oxidation.
[0053] (8) Conduct characterization tests on the samples.
[0054] Figure 1 (a) is a schematic diagram of the 3D printing process of the inorganic salt-based copper precision device of the present invention and (b) is a SEM image of the surface of the copper precision device structure. It can be seen that the copper component manufactured by the present invention has a high surface density and low roughness. From the (c) EDX element analysis spectrum, it can be seen that the copper component manufactured by the present invention has a high purity. The remaining impurity elements are inevitable in the sintering process and have reached the highest purity among similar technologies.
[0055] Figure 2 The EBSD spectrum of the surface of the copper precision device structure (a) shows that there are concentrated micron twins and the grain size is relatively uniform. This structure is of great help in improving the conductivity and mechanical strength of the copper component. From the nanoindentation hardness diagram based on the Hall-Patch curve (b), it can be seen that the hardness of the copper component is significantly higher than the theoretical curve, indicating that the copper component manufactured by the present invention has excellent mechanical properties.
Claims
1. A method for additive manufacturing of copper precision devices based on inorganic salts, characterized in that: The specific steps include: (1) Preparation of copper-carrying photosensitive resin: Polyethylene glycol diacrylate oligomer with a molecular weight of 575, photoinitiator PI-819, dye lemon yellow and diluent deionized water are mixed evenly to form a copper-carrying photosensitive resin, wherein the mass of the diluent is 2-3 times the mass of the oligomer, and the added amounts of the photoinitiator and dye are 1wt% and 0.05wt% of the oligomer, respectively; (2) Printing of copper precision device hydrogel precursor: according to the preset model parameters of the copper precision device, the copper-carrying photosensitive resin is placed in a 3D printer for 3D printing to obtain the copper precision device hydrogel precursor; (3) Copper ion loading: The copper precision device hydrogel precursor is fully immersed in a 0.8-1.1 mol / L CuSO4 solution and washed with water to obtain a copper-loaded organic metal structure device; (4) Thermal degreasing treatment of copper-loaded organic metal structure devices: Place the copper-loaded organic metal structure device in a muffle furnace, raise the temperature to 700±50°C in an air atmosphere, remove organic matter in the copper-loaded organic metal structure device, and then cool it naturally to room temperature; (5) Copper ion reduction treatment of copper-loaded organic metal structure devices: The copper-loaded organic metal structure device after the thermal degreasing treatment in step (4) is placed in a tube furnace, and the temperature is raised to 900±50°C in an inert atmosphere to reduce the copper ions and further remove impurities in the device, and then naturally cooled to room temperature to obtain a copper precision device.
2. The method for additive manufacturing of copper precision devices according to claim 1, characterized in that: In step (2), the printing parameters are as follows: printer light wavelength: 405nm; printing layer thickness: 0.05mm; substrate light intensity: 30 mW / cm 2 ; The light intensity of the remaining layers is 10 mW / cm 2 ; Exposure time of substrate: 2.5s; Exposure time of other layers: 5.5s; Platform separation speed: 3mm / s; Waiting time after separation: 5s; Post-curing time: 10min.
3. The method for additive manufacturing of copper precision devices according to claim 1, characterized in that: In step (3), the concentration of the CuSO4 solution is 1.0 mol / L, the soaking temperature is 50°C, and the soaking time is 3-5 days.
4. The method for additive manufacturing of copper precision devices according to claim 1, characterized in that: In step (4), the insulation time is 2 to 3 hours.
5. The method for additive manufacturing of copper precision devices according to claim 1, characterized in that: In step (5), the heating rate is below 1°C / min, and the temperature is kept at 500°C for 2h.
6. The method for additive manufacturing of copper precision devices according to claim 1, characterized in that: In step (5), the insulation time is 9 to 10 hours.
Citation Information
Patent Citations
Manufacturing method of pure copper 3D printing additive material
CN109759589A